Future Directions in Eubalaena spp.: Comparative Research to Inform Conservation - Harcourt, Rob; van der Hoop, Julie; Kraus, Scott; Carroll, Emma L. (Frontiers in Marine Science, 2019)
All three extant right whales (Eubalaena australis (Southern; SRW), glacialis (North Atlantic; NARW), and japonica (North Pacific; NPRW)) were heavily exploited, and the status of the two northern hemisphere species remains precarious. Limited gains made by the NARW have been reversed and urgent changes to management approaches are needed to avert extinction. By contrast, some SRW populations are recovering. Given their close phylogenetic relationship, morphological, demographic, and ecological similarities, the contrasting recovery rates suggest a comparative approach. 1. Recovery Right whales were protected in 1931, but NARW, NPRW and some SRW populations have barely recovered from whaling, while others are doing well. Are these differences a legacy of extreme depletion (e.g., loss of genetic diversity and cultural knowledge) or primarily due to anthropogenic factors (e.g. ship strike and fisheries entanglement). If modern anthropogenic threats are not affecting remote SRW populations, inform on NARW and NPRW? 2. Linking individuals to population level responses In the context of life history strategies strong links exist between reproductive indices and environmental conditions. Tracking survival, reproduction and other demographic parameters, and their population-level consequences, is possible with Individual identification. Robust life-history analyses link demography with environmental conditions, potentially teasing out influencing factors. 3. Adapting to shifting resources Recent reproductive declines in NARW appear linked to changing food resources and prey phenology. We know some large-scale movement patterns for NARW and a few SRW populations, we know little of mesoscale movements. For NPRW and some SRW populations, even broad-scale movements are poorly understood. In the face of climate change, can methodological advances help identify distributional and migratory responses? 4. Emergent diseases and the vulnerability of populations under stress Marine mammals are vulnerable to infectious diseases, particularly when subjected to stressors such as fishing gear entanglements, acoustic disturbance, and prey shortages. New tools to assess large whale health include body condition imaging, viromes, microbiomes, and stress hormones. 5. Comparative synthesis and cumulative effects A good cumulative effects analytical approach is urgently required, otherwise each stressor is managed in isolation, limiting efficacy. We propose a comparative synthesis to inform future cumulative effect analyses and outline future research priorities.